COMPARISON OF THE COURSE BOOKS PREPARED AT THE SAME CLASS LEVEL IN TERMS OF ATTACHMENTS AND DISCOUNTS - Selbi ATALAN (Fırat University, 2021)
Turkish is a rich language in terms of vocabulary. The biggest indicator of this vocabulary in practice is proverbs and idioms. Proverbs and idioms are a cultural transmitter that reveals the vitality of the language and enables students to bridge the past and the future. Proverbs and idioms, which have an important place in our language, are conveyed to students through textbooks in schools, although they are conveyed in different ways in the oral and written tradition. In this respect, students should be brought together with publications containing rich vocabulary and vocabulary elements that reflect the power of narration and rich content. The most common tool that brings these texts together with students is the compulsory textbooks that MEB distributes to all students free of charge. These books are written by private publishers or MEB publications and published with the approval of the Board of Education and Discipline. The aim of this research is to compare the similarities and differences of three 7th grade Turkish textbooks prepared by two different publishers in terms of idioms and proverbs. The research is a qualitative research. The universe of the research is the books (7th grade Turkish textbooks prepared by MEB (2) and Özgün ”publishing houses) which were accepted as textbooks for 7th grades of primary schools in 2019-2020 by the Ministry of Education Board of Education and Discipline. The presence of idioms and proverbs in three books was determined by content analysis through TDK Proverbs and Idioms Dictionary. According to the results obtained, it was observed that the textbooks prepared by different publishing houses were not sufficient to provide students with the same vocabulary in the same grade level.